Answer:
inverse = ( log(x+4) + log(4) ) / (2log(4)), or
c. y = ( log_4(x+4) + 1 ) / 2
Explanation:
Find inverse of
y = 4^(-6x+5) / 4^(-8x+6) - 4
Exchange x and y and solve for y.
1. exchange x, y
x = 4^(-6y+5) / 4^(-8y+6) - 4
2. solve for y
x = 4^(-6y+5) / 4^(-8y+6) - 4
transpose
x+4 = 4^(-6y+5) / 4^(-8y+6)
using the law of exponents
x+4 = 4^( (-6y+5) - (-8y+6) )
simplify
x+4 = 4^( 2y - 1 )
take log on both sides
log(x+4) = log(4^( 2y - 1 ))
apply power property of logarithm
log(x+4) = (2y-1) log(4)
Transpose
2y - 1 = log(x+4) / log(4)
transpose
2y = log(x+4) / log(4) + 1 = ( log(x+4) + log(4) ) / log(4)
y = ( log(x+4) + log(4) ) / (2log(4))
Note: if we take log to the base 4, then log_4(4) =1, which simplifies the answer to
y = ( log_4(x+4) + 1 ) / 2
which corresponds to the third answer.